Histological Scoring of Rectal Mucosa by Digital Quantitative Method in Bangladeshi Subjects - Chowdhury, MMH; Alim, MA; Haque, MA; Rahman, MK; Mahmood, I; Rashid, MH; Khan, MMR; Kamal, M (TAJ: Journal of Teachers Association, 2009)
Chronic inflammation is characterized by increased numbers of round cells in lamina propria, associated with irregularity of glandular system and increasing number of glands per area. But still there is no objective way to demarcate between normal and diseased mucosa by counting the number of inflammatory cells. Until date it is done arbitrarily which depends primarily upon the knowledge and experience of pathologist. So this study has been done with aims to score normal rectal mucosal histology using digital quantitative methods in Bangladeshi subjects. The variable recorded were the diameter of ten consecutive transversely cut glands, the space of lamina propria between glands and number of gland per high power field .Thirty patients with ankylosing spodylitis having normal rectal mucosa were enrolled for histological.scoring by digital quantitative methods. In this study it is found that 90% of subjects have the score of 17 or less. This data obtained serve as a basis for demarcating the histological state of rectal mucosa from various chronic inflammatory condition of rectum. TAJ 2009; 22(1): 190-193